Identification of MAP3K4 as a novel regulation factor of hepatic lipid metabolism in non-alcoholic fatty liver disease - Zhiyong He; Yangyang Bin; Guangshun Chen; Qiang Li; Wenling Fan; Yongqiang Ma; Junfang Yi; Xiaohua Luo; Zhi Tan; Jiequn Li (Journal of Translational Medicine, 2022)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is a metabolic disorder with abnormal lipid metabolism. The present study was to identify regulatory genes related to lipid droplets (LDs) abnormal accumulation in NAFLD. Methods transcriptomic analysis and bioinformatics analysis (GEO database) were used to identify potential genes in abnormal lipid metabolism of NAFLD. A candidate gene MAP3K4 expression were detected by immunohistochemistry staining in NAFLD and controls. RNA interference and immunoblotting were used to verify the roles of MAP3K4 in the formation of hepatic LDs. Results A total of 134 candidate genes were screened, including 44 up-regulated genes and 90 down-regulated genes. 29 genes in the protein–protein interaction (PPI) were selected as hub genes, including MAP3K4. The expression levels of MAP3K4 were positively correlated with NAFLD activity score (r = 0.702, p = 0.002). Furthermore, we found a positive correlation of MAP3K4 expression with serum total cholesterol (r = 0.564, p = 0.023), uric acid levels (r = 0.520, p = 0.039), and body mass index (r = 0.574, p = 0.020). Downregulation of MAP3K4 decreased LDs accumulation in HepG2 cells and reduced the expression of CGI-58 and Plin-2 by imbibition of JNK and group IVA cytosolic phospholipase A2 (cPLA2) activation. Conclusion The study revealed a number of regulatory genes related to hepatic lipid metabolism of NAFLD, and demonstrated that MAP3K4 played a pivotal role in the hepatic lipogenesis of NAFLD.